Raising Environmental Consciousness and Its Impact on Adolescence Interpersonal Dynamics in Wendelin van Draanen's 'Flipped' - Qonita Nowindra Ramadhani; Henrikus Joko Yulianto (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study investigates the intricate relationship between environmental identity and adolescence interpersonal dynamics within Wendelin van Draanen's novel "Flipped," examining how the natural world shapes psychological well-being and social connections through the framework of Environmental Identity Theory (Clayton, 2003) . The research aims to analyze the portrayal of the sycamore tree as a key environmental element influencing the protagonist's psychological states, and how her unique environmental identity shapes adolescent relationships. Furthermore, it explores how differing perceptions and treatments of the environment by various adolescent characters manifest distinct psychological impacts, contributing to conflicts and connections, as interpreted through the lens of Environmental Identity Theory. Employing a qualitative, text-based approach, this review article analyzes the novel "Flipped" as the primary research subject. Data collection involved close reading and thematic analysis of the novel's text, focusing on dialogue, character descriptions, and narrative events related to environmental interactions, attitudes, and the formation of self in relation to nature. The analysis reveals that the sycamore tree serves as a significant anchor for the protagonist's developing environmental identity, fostering deep emotional responses that influence her interpersonal interactions. It also highlights how varied environmental consciousness, shaped by differing environmental identities, leads to divergent psychological impacts among characters, influencing their conflicts and the development of connections. This research contributes to understanding how environmental identity formation in adolescence, as depicted in literature, significantly impacts social relationships and psychological well-being.